BeagleBone Black Cookbook - Hamilton, Charles A.; Hamilton, Charles A. (Packt Publishing, 2015)
Over 60 recipes and solutions for inventors, makers, and budding engineers to create projects using the BeagleBone BlackAbout This BookLearn how to develop applications with the BeagleBone Black and open source Linux softwareSharpen your expertise in making sophisticated electronic devicesExplore the BeagleBone Black with this easy-to-succeed recipe formatWho This Book Is ForIf you are a hardware, Linux, and/or microcomputing novice, or someone who wants more power and possibilities with product prototypes, electronic art projects, or embedded computing experiments, then this book is for you. It is for Internet of Things enthusiasts who want to use more sophisticated hardware than the Raspberry Pi or the Arduino can provide.Whether you are an engineering student, a DIYer, an inventor, or a budding electronics enthusiast, this book delivers accessible, easy-to-succeed instructions for using an advanced microcomputing platform.What You Will LearnSet up and run the BeagleBone Black for the first timeLearn the basics of microcomputing and Linux using the command line and easy kernel modsMake introductory projects with Python, JavaScript, BoneScript, and Node.jsExplore physical computing and simple circuits using buttons, LEDs, sensors, and motorsDiscover the unique features of the BeagleBone Black and its real-time computing functionsBuild intermediate level audio and video applicationsAssemble and add ingredients for creating Internet of Things prototypesIn DetailThere are many single-board controllers and computers such as Arduino, Udoo, or Raspberry Pi, which can be used to create electronic prototypes on circuit boards. However, when it comes to creating more advanced projects, BeagleBone Black provides a sophisticated alternative. Mastering the BeagleBone Black enables you to combine it with sensors and LEDs, add buttons, and marry it to a variety of add-on boards. You can transform this tiny device into the brain for an embedded application or an endless variety of electronic inventions and prototypes.With dozens of how-tos, this book kicks off with the basic steps for setting up and running the BeagleBone Black for the first time, from connecting the necessary hardware and using the command line with Linux commands to installing new software and controlling your system remotely. Following these recipes, more advanced examples take you through scripting, debugging, and working with software source files, eventually working with the Linux kernel. Subsequently, you will learn how to exploit the board's real-time functions. We will then discover exciting methods for using sound and video with the system before marching forward into an exploration of recipes for building Internet of Things projects. Finally, the book finishes with a dramatic arc upward into outer space, when you explore ways to build projects for tracking and monitoring satellites.Style and approachThis comprehensive recipe book deconstructs a complex, often confusing piece of technology, and transforms it to become accessible and fun with snappy, unintimidating prose, and extensive easy-to-succeed instructions.